Thermochemical and structural studies of gallic and ellagic acids - Dávalos J.Z. (2019)
J.Z.D acknowledges the support funding to IQFR-CSIC (Spain) and peruvian CONCYTEC (INNÓVATE PERÚ, ECIP-1-P-030-14 Grant).